Hydrological impacts of climate change on the future streamflow of three unregulated catchments of the Australian hydrologic reference stations - Al-Safi, H.I.J.; Sarukkalige, Ranjan (2019)
Copyright © 2019 Inderscience Enterprises Ltd. A physically-based distributed hydrological model (BTOPMC) is adopted to assess the impact of climate-change on the hydrological-behaviour of three-contributing catchments of the Australian hydrologic reference stations (HRSs). Both historical and future streamflow trends are compared and discussed. Firstly, the BTOPMC-model was calibrated and validated based on the observed hydro-meteorological data from the three-catchments. The calibrated BTOPMC-model was then forced with the downscaled future climate signals from a multi-model ensemble of eight-GCMs of the CMIP5 under the RCP4.5 and RCP8.5 scenarios to simulate the future daily streamflow at the three-HRSs for the mid (2046-2065) and late (2080-2099) of the 21st-century. Nearly all GCMs predict a reduction-tendency in mean-annual rainfall and an increase in temperature and potential-evapotranspiration across the studied catchments. The mean annual-streamflow also shows reductiontendencies during the future-periods ranged between 26%-53% at Dingo-Road HRS, 10%-25% at Haystack-HRS and 6%-33% at Coggan-HRS relative to the control-run.